Tendencies in Research on Innovation in Low-Technology Sectors - Marcin Żemigała (Operations Research and Decisions, 2018)
The aim of the article is to identify and analyse the main tendencies in and subject matter of research on innovation in low-technology sectors. The data analysed come from the Scopus database covering 1977-2015. The author concentrates on the dynamics of the numbers of such research articles, the major academic fields applied in this research, together with the industrial sectors, countries and topics studied. With respect to temporal dynamics, it is clear that the overall trend is growth, with more and more articles being published on innovation in low-tech sectors. These studies are concentrated mainly within four academic areas: business, management and accounting; economics, econometrics and finance; social sciences; engineering. As far as industrial sectors are concerned, the food industry is the most common subject of interest. The United States and Great Britain can be clearly identified as the countries most often studied. The main topics discussed concern technical issues related to new products, interactions between industry and research centres, together with aspects of innovation by managers and enterprises. (original abstract)